Riociguat in children with pulmonary arterial hypertension: the PATENT-CHILD study - Garcia-Aguilar, Humberto; Gorenflo, Matthias; Ivy, D. Dunbar; Moledina, Shahin; Castaldi, Biagio; Ishida, Hidekazu; Cześniewicz, Paweł; Kusa, Jacek; Miera, Oliver; Pattathu, Joseph George; Weng, Ken-Pen; Ablonczy, Laszlo; et al. (Pulmonary circulation, 2022)
Riociguat, a soluble guanylate cyclase stimulator, is approved for treatment of adults with pulmonary arterial hypertension (PAH). The safety, tolerability, and pharmacokinetics (PK) of oral riociguat in a pediatric population with PAH was assessed in PATENT-CHILD (NCT02562235), a multicenter, single-arm, 24-week, open-label, Phase 3 study.